The marketing planning workbook : effective marketing for marketing managers - Dibb, Sally; Simkin, Lyndon; Bradley, John (London : Routledge, 1996)
Business
2003-04-21
Keywords: Marketing-Planning; Marketing environment; Marketing strategy